Maternaly-child feeding practices and associations with maternal and child characteristics - Gonçalves, Sónia (2017)
We evaluated associations between maternal child-feeding practices and maternal (age, body mass index [BMI], education, disordered eating) and child (age, BMI, emotional and behavioral) characteristics in 412 mothers and their children using the Parental Feeding Practices, the Child Behavior Checklist, and the Eating Disorders Examination Questionnaires. Maternal BMI was positively correlated with covert control feeding practices. Younger maternal age and lower maternal educational level were associated with increased maternal pressure to eat and overt control in their child-feeding practices. Maternal disordered eating behaviors were associated with increased restriction and covert control in their child-feeding practices. Maternal monitoring during child feeding was associated with lower levels of the child's problems with internalization and externalization. Finally, maternal feeding practices that involved covert control were related to higher eating restriction by the mother on herself and more maternal concern about her child's weight. Our findings suggest that maternal feeding practices such as overt and covert control are related to both maternal and child factors. Clinicians must become aware that these maternal feeding practices can model children's eating behavior and disrupt children's self-regulation of food intake; however, maternal monitoring during child feeding seems to be related to children's well-being.